EDUCATION AS A KEY FACTOR IN HUMAN CAPITAL DEVELOPMENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article analyzes the essence of human capital, its importance today, the development of human capital and the positive results that can be achieved as a result. Also, proposals were made to raise the education system, which plays an important role in the development of human capital, to a new level in line with modern requirements, to train qualified personnel for new professions emerging in the labor market.